Problematika Kemampuan Literasi Membaca Siswa Sekolah Dasar - Zakiah, Hida Ma'rifatuz; Sukmandari, Yesi (TSAQOFAH, 2024)
Reading is an activity that has the aim of understanding the content of what is written and is also a skill that elementary school students must master because with good reading skills students can learn a lot of knowledge. The purpose of writing this journal is to describe the problematic factors of low reading ability in elementary school students. This type of research is qualitative research using the library study method, with data collection techniques from various reading sources in the form of articles on various types of problems in elementary schools. The research results show that 1) The first problematic cause of low reading ability is students' low interest in reading, books that are less interesting to students, inadequate libraries, short reading time of only 15 minutes. 2) The role of parents in increasing literacy, is providing motivation and encouragement, 3) The role of teachers in increasing literacy, providing media and methods that attract students' interest, teachers providing reading corners in the classroom.